Implementasi Aksi Kolaborasi Mahasiswa Program Kampus Mengajar Angkatan 8 Tahun 2024 - Kurniasari, Septiana; Susilo, Bragas Genta Arya; Utiah, Israwati; Eato, Meisti Fani; Habibi, Moh. Arif Alfan (Yayasan Daarul Huda Kruengmane, 2024)
Education in Indonesia still experiences many gaps and lags compared to other countries. One of the programs of the MBKM policy is Kampus Mengajar, which aims to help improve the quality of education in elementary, junior high, and senior high schools/vocational schools. The purpose of this activity is to find out the implementation of collaborative actions by Kampus Mengajar Batch 8 students, in an effort to improve numeracy literacy, administration, technology adaptation, student character development, and environmental conservation. The data used is qualitative data using descriptive methods. The Kampus Mengajar Batch 8 program will be implemented in September - December 2024. The stages of implementing activities include planning, implementation and evaluation. The implementation of the collaborative action of the Kampus Mengajar Batch 8 program in 2024 went very well and had an impact, especially on the academic abilities of students. In addition, this collaborative action succeeded in creating a very good emotional bond between teachers, students and students.